1991
DOI: 10.1111/j.1365-2109.1991.tb00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between condition factor and total lipid content in Atlantic salmon, Salmo salar L., parr

Abstract: Abstract. A strong and significant positive correlation was observed between condition factor and total lipid content in immature Atlantic salmon, Salmo salar L., parr (0+) sampled at the same time. Condition factor can thus be used as a convenient non‐lethal indicator of energy reserve status among immature salmonids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 12 publications
5
71
0
Order By: Relevance
“…In fish, non-polar lipid density is typically used as a measure of an individual's energetic state because it is the main energy source utilized during periods of starvation, reproduction, and maturation (Wootton et al 1978, Reznick & Braun 1987, Norton et al 2001. Several studies have confirmed a relationship between K or K n and non-polar lipid density, including in three-spined stickleback Gasterosteus aculeatus (Chellappa et al 1995), striped bass Morone saxatilis (Gershanovich et al 1984, Brown & Murphy 1991, broad whitefish Coregonus nasus (Fechhelm et al 1995), ship sturgeon Acipenser nudiventris (Gershanovich et al 1984), muskellunge Esox masquinongy (Jonas et al 1996), and Atlantic salmon Salmo salar (Pinder & Eales 1969, Herbinger & Friars 1991, Kadri et al 1995. However, Simpson et al (1992) and Sutton et al (2000) showed that in Atlantic salmon, the strength of the correlation between the condition factors and lipid density varied during the season, stressing the importance of determining an association at critical periods, such as at the onset of breeding for studies of mating systems and reproductive success.…”
Section: Introductionmentioning
confidence: 89%
“…In fish, non-polar lipid density is typically used as a measure of an individual's energetic state because it is the main energy source utilized during periods of starvation, reproduction, and maturation (Wootton et al 1978, Reznick & Braun 1987, Norton et al 2001. Several studies have confirmed a relationship between K or K n and non-polar lipid density, including in three-spined stickleback Gasterosteus aculeatus (Chellappa et al 1995), striped bass Morone saxatilis (Gershanovich et al 1984, Brown & Murphy 1991, broad whitefish Coregonus nasus (Fechhelm et al 1995), ship sturgeon Acipenser nudiventris (Gershanovich et al 1984), muskellunge Esox masquinongy (Jonas et al 1996), and Atlantic salmon Salmo salar (Pinder & Eales 1969, Herbinger & Friars 1991, Kadri et al 1995. However, Simpson et al (1992) and Sutton et al (2000) showed that in Atlantic salmon, the strength of the correlation between the condition factors and lipid density varied during the season, stressing the importance of determining an association at critical periods, such as at the onset of breeding for studies of mating systems and reproductive success.…”
Section: Introductionmentioning
confidence: 89%
“…In this respect K alone can dictate different quality grades at processing and is regularly assessed during on-growing to achieve quality targets. Importantly K is also a recognized indicator of nutritional status in Atlantic salmon where it correlates positively with dietary energy fed (Young et al, 2006) and total flesh lipid at the parr stage (Herbinger and Friars, 1991). In teleosts, the accepted form of weight-length relationships (WLR): BW=aFL b , where BW and FL are body size variables and a and b are parameters of the relationship (Froese, 2006), also expresses variations in K over a population size range.…”
Section: Introductionmentioning
confidence: 99%
“…However, condition indices can be useful if used correctly by minimizing sources of variability. For example, the K factor has been used as an indicator of recent feeding activity (Cone 1989), body energy reserves (Neff and Cargnelli 2004, Pangle and Sutton 2005, Herbinger and Friars 2008, energy densities (Trudel et al 2005) and physiological conditions (Rennie and Verdon 2008). In comparison, the advantages of Wr are that the standard weight compensates for inherent changes in the body form, and its values can be compared between fish of different lengths and from different populations (Ney 1999, Blackwell et al 2000.…”
mentioning
confidence: 99%